Benchmarking in the logistics management system of Ukrainian enterprises - ZRYBNIEVA, IRYNA; Pichugina, J., Sigaieva, T., Saienko, V., & Korolkov, V. (Amazonia Investiga, 2023)
The relevance of this study is manifested in the need of Ukrainian logistics companies to effectively manage and increase their competitiveness. Establishing benchmark enterprises and applying benchmarking allows identifying best practices and management principles. The use of statistical data on the economic and economic activity of the logistics industry allowed for statistical, parametric and correlation analyzes, which contributes to an objective study of trends in the transport and logistics industry of Ukraine. The proposed hypothesis on the use of a wide sample of statistical data reflects the potential for developing an algorithm and implementing the benchmarking methodology in the logistics industry management system. It is found that motor transport enterprises occupy leading positions in the Ukrainian market of transport and logistics services. Freight and logistics services, in particular transportation of ore products, prevail in the field of motor transport. The analysis of regional peculiarities revealed that Dnipropetrovska oblast, Kyiv and Donetsk oblast are favorable for freight and logistics activities. It was also found that privately owned companies predominate among the specialized enterprises in this industry. The benchmarking analysis confirmed that it is possible to use profile data to identify benchmark enterprises with the best economic performance and to use their experience to improve the competitiveness of other companies. Such analysis reveals the strengths and weaknesses of enterprises, provides opportunities for improvement and development, and facilitates informed decision-making to improve the productivity and quality of logistics processes. Thus, the benchmarking methodology proves to be an effective tool for assessing and comparing the economic and financial performance of logistics companies, contributing to their competitiveness and market position.
Keywords: benchmarking analysis, logistics industry, economic efficiency, competitiveness, statistical analysis